4‐(4‐Hydroxyphenyl)‐2‐butanol (rhododendrol)‐induced melanocyte cytotoxicity is enhanced by UVB exposure through generation of oxidative stress. Issue 7 (28th June 2018) - Goto, Noriko; Tsujimoto, Mariko; Nagai, Hiroshi; Masaki, Taro; Ito, Shosuke; Wakamatsu, Kazumasa; Nishigori, Chikako
Abstract: 4‐(4‐Hydroxyphenyl)‐2‐butanol (rhododendrol, RD), a skin‐whitening agent, was reported to cause skin depigmentation in some users, which is attributed to its cytotoxicity to melanocyte. It was reported that cytotoxicity to melanocyte is possibly mediated by oxidative stress in a tyrosinase activity‐dependent manner. We examined the effect of UV radiation (UVR) on RD‐induced melanocyte cytotoxicity as an additional aggravating factor. UVR enhanced RD‐induced cytotoxicity in normal human epidermal melanocytes (NHEMs) via the induction of endoplasmic reticulum (ER) stress. Increased generation of intracellular reactive oxygen species (ROS) was detected. Pretreatment with N‐acetyl cysteine (NAC), antioxidant and precursor of glutathione significantly attenuated ER stress‐induced cytotoxicity in NHEMs treated with RD and UVR. Increase in cysteinyl‐RD‐catechol and RD‐pheomelanin in NHEMs treated with RD and UVR suggested that, after UVR excitation, RD or RD metabolites are potent ROS‐generating substances and that the tendency to produce RD‐pheomelanin during melanogenesis amplifies ROS generation in melanocytes. Our results help to elucidate the development mechanisms of RD‐induced leukoderma and provide information for innovation of safe skin‐whitening compounds.